(untitled) (Global Journal of Human-Social Science, 2024)
In this paper the general objective is to highlight the development of the capital market and its relations with industry in Brazil between the end of the 19th century and the beginning of the 20th century The underlying hypothesis is that the capital markets in Rio de Janeiro and S o Paulo were driven by changes in legislation and institutions created at the time Due to these changes transactions on Stock Exchanges have become an important attraction for companies It is concluded that the national capital market was decisive in stimulating Brazilian industry in the period with both changes in legislation and institutions being the fundamental links in this connection